Konstruksi Makna Kegiatan “Traveling & Teaching” Komunitas 1000 Guru oleh Relawan - Allegra Gabriella Esther; Hanny Hafiar; Heru Riyanto Budiana (Jurnal Nomosleca, 2018)
AbstractThis research is based on a phenomenon in traveling teaching activities by the 1000 Teachers Community, a community that cares about education in the interior and borders of Indonesia. In this activity, volunteers will pay a fee to go to one of the interior in Indonesia, stay for three days and two nights and teach children in schools that need help. In this study, it can be seen how volunteers interpret traveling teaching. Using the constructivist paradigm with the types of phenomenological studies and phenomenological theories. The results of this study indicate that the meaning is divided into three, namely the meaning as an activity, an educational caring activity, and an understanding of education in the interior, besides that there is a meaning of the 1000 Teacher Community which also influences volunteers in interpreting traveling teaching. Keyword : meaning construction, interpreting, education communicationDOI : https://doi.org/10.26905/nomosleca.v4i1.1795